PENGARUH PEMAHAMAN EKONOMI, DAN PEMAHAMAN LITERASI TERHADAP KECERDASAN FINANCIAL PADA MAHASISWA PENGHAFAL ALQUR’AN - Priyo Utomo; Syamsul Arifin (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
Economic understanding contains basic economic lessons in general, namely economic problems, national income, markets and so on while financial literacy includes knowledge of finance that includes financial institutions and the Financial Services Authority, systems and means of payment, inflation and price indexes and markets, capital. The purpose of the study was to reveal the influence of Economic Understanding, Financial Literacy, on The Financial Intelligence of Students of the Campus entrepreneur memorizing the Qur'an (KEPQ), the method in this research uses a quantitative approach with the type of research used is expost facto. The research was conducted at the Entrepreneur Campus memorizing the Qur'an (KEPQ) Surabaya, a population of 120 people and a research sample of 93 people determined by proportional random sampling techniques. From the results of the study Partially there is a positive influence between economic understanding (X1) on intelligence financial (Y). and there is no influence of financial literacy (X2) on financial intelligence (Y). While simultaneously variable economic understanding (X1), financial literacy (X2), affects financial intelligence (Y). So it can be concluded when understanding the economy, increased financial literacy will affect the increasing financial intelligence of students